3-Hydroxy-3-Methylglutaryl-CoA Reductase Enzyme Inhibitors for Prevention of Contrast-Induced Nephropathy: A Meta-Analysis of Prospective Randomized Controlled Studies. (November 2015) - Briasoulis, Alexandros; Mallikethi-Reddy, Sagar; Sharma, Shikha; Briasouli, Artemis A.; Afonso, Luis
Abstract : Contrast-induced nephropathy (CIN) is a possible complication of interventional procedures that require administration of an iodinated contrast. Previous observational and small prospective randomized trials suggested that 3-hydroxy-3-methylglutaryl-CoA reductase enzyme inhibitors may reduce the incidence of CIN. We performed a meta-analysis of the effect of statins on CIN including prospective randomized, controlled trials of statin therapy. We conducted an EMBASE and MEDLINE search for studies in which patients were randomized to treatment with a statin plus standard treatment (or placebo) versus standard treatment (or placebo). We included studies that provided data on creatinine clearance, and incidence of CIN before the initiation of the treatment and at the end of the follow-up period. We identified 9 prospective randomized studies of high-dose statin treatment compared with placebo treatment for CIN prevention with 2504 controls and 2480 patients that received statins. A significant reduction in CIN was observed when pharmacologic intervention with statins was used (odds ratio, 0.45; 95% confidence interval, 0.34–0.58; P < 0.0001). In this meta-analysis of prospective controlled studies, we found a statistically significant reduction of CIN incidence in patients pretreated with high-dose statins before the procedure.